Climatic Factors and the Incidence of Pyelonephritis During Pregnancy - John D. Busowski; Ronald A. Chez (Hindawi Limited, 1995)
Objective: Numerous published reports have linked various disease states and pregnancy-related conditions with meteorologic factors such as weather, humidity, and temperature. The purpose of this study was to determine if temperature and dew point affect the incidence of pyelonephritis during pregnancy.